Estimation of stature from hand length and breadth- An anthropometric study on 100 Bangladeshi adult Muslim males of lower socioeconomic status group (Journal of Dhaka National Medical College & Hospital, 2015)
Body physique is influenced to a greater extent by climatic, hereditary, nutritional and racial factors. The stature prediction occupies relatively a central position in the anthropometric research and estimation of stature of an individual from mutilated or amputated limbs has obvious significance in the personal identification in the events of murders, accidents or natural disasters. The present study was undertaken to measure the stature as well as some length and breadth of hand and to determine whether there is any correlation between stature and the hand variables and to estimate the stature using respective multiplication factor from these variables and to assess the effectiveness of the above estimations by comparing the 'estimated' values with the 'measured' values.It is descriptive type of study. The study was carried out with a total number of 100 Bangladeshi adult Muslim males of age between 25 to 30years of lower socio-economic status group. The analyses were conducted in the Department of Anatomy of BSMMU, Dhaka during the study period of January 2006 to December 2006.Hand length and breadth along with their stature were measured directly from The subjects by using Anthropometric sliding caliper, steel plate and measuring tape. The data were then statistically analyzed by computation to find out its normative value. Multiplication factors were estimated for estimating stature and comparisons were made between measured and estimated stature using paired "t" test.The mean measured values of the length and breadth of right and left and hands as well as the stature were 18.04(±0.71)cm, 17.99 (+±9.08)cm, 8.06 (±0.26)cm, 7.98 (±0.27)cm, and 163.70 (±5.98)cm, respectively were found. The multiplication factors were estimated for the same hand measurements with the stature. Significant positive correlations were found between stature and hand variables and the differences between the measured value and estimated values were not statistically significant.J.Dhaka National Med. Coll. Hos. 2015; 21 (02): 24-29